PENSA study for the prevention of cognitive decline in APOE‐ɛ4 carriers with subjective cognitive decline: Baseline preliminary demographic and neuropsychological description of the study population. (December 2021) - Forcano, Laura; Soldevila‐Domenech, Natalia; Cuenca, Aida; Lorenzo, Thais; Boronat, Anna; Piera, Iris; Puig‐Pijoan, Albert; Knezevic, Iva; Fauria, Karine; Molinuevo, Jose; de la Torre, Rafael
Abstract: Background: In the absence of effective treatments to reverse cognitive deterioration related to Alzheimer's disease (AD), nonpharmacological secondary prevention interventions at early preclinical stages have been found to be a promising strategy to prevent cognitive decline. In this context, the PENSA study, framed within the WW‐FINGERS consortium, is a randomized clinical trial involving cognitively normal elderly individuals with an increased risk of developing AD (meeting subjective cognitive decline, SCD‐plus criteria and being APOE‐ɛ4 carriers). The aim of the study is to evaluate the efficacy of a multimodal personalized lifestyle intervention (dietary and physical activity counseling and cognitive training) combined with a dietary supplement, epigallocatechin gallate (EGCG) in slowing down cognitive decline. Method: In this work we present the baseline sociodemographic, mood and cognitive characteristics of the already enrolled sample. Cognitive function was measured with the Alzheimer Disease Cooperative Study Preclinical Alzheimer Cognitive Composite (ADCS‐PACC) and adding to this original version the interference score from the Stroop Color and Word Test and the Five Digit Test (ADCS‐PACC‐Plus‐exe). Additionally, the Digit Span, the Boston Naming Test and the Animal Fluency Test were administered. Psychological distress was measured with the Hospital Anxiety and Depression Scale. Result: On January 2021 the study had enrolled 68 individuals (62% women) with a mean (SD) age of 67.4 (4.6) years and the following APOE genotype: 83% ɛ3/ɛ4, 13% ɛ4/ɛ4 and 4% ɛ2/ɛ4. Most had higher education (66.2%) and 84% were retired (Table 1). Mild and moderate symptoms of psychological distress were present in 14.7% and 23.5% of participants, respectively. The mean (SD) number of cognitive domains affected (memory, concentration, language, visuospatial skills), measured by an ad‐hoc SCD questionnaire, were 2.54 (±0.9). 77.3% of participants referred memory centered complaints. Considering the different domains, participants reported alterations on memory (97.1%), concentration (73.5%), language (67.6%) and visuospatial skills (11.8%). SCD profiles are shown in Figure 1. Table 2 shows the ADCS‐PACC‐Plus‐exe scores. Conclusion: The PENSA study will provide valuable information on the effect of a lifestyle intervention supplemented with EGCG to prevent cognitive decline and will aid to share light on the benefit of these strategies in people at‐risk of developing AD.